Leptin and leptin receptor: Analysis of a structure to function relationship in interaction and evolution from humans to fish - Prokop, JW (2012)
Leptin is a circulating protein which regulates dietary intake through binding the leptin receptor. Numerous labs have used known structures and mutagenesis to study this binding process in common animal models (human, mouse and rat). Understanding this binding process in other vertebrate species will allow for a better understanding of leptin and leptin receptor function. The binding site between leptin and leptin receptor is highly conserved in mammals as confirmed through sequence alignments mapped onto structures of both leptin and leptin receptor. More variation in this interaction is found in lizard and frog sequences. Using our models, we show that the avian leptin sequences have far less variation in the binding site than does the leptin receptor. This analysis further suggests that avian leptins are artifactual. In fish, gene duplication events have led to the expression of multiple leptin proteins. These multiple leptin proteins have variation in the regions interacting with leptin receptor. In zebrafish and the Japanese rice fish, we propose that leptin A has a higher binding energy than does B. Differing binding energies are evidence of either divergent functions, different binding confirmations, or other protein partners of leptin B.